2020
DOI: 10.1088/1742-6596/1559/1/012096
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative study of transport current loss in HTS coils for superconducting wireless power transfer

Abstract: This paper focuses on the transport current loss modelling for HTS coated conductor coils under high-frequency AC current, which is essential when applying superconducting technology in wireless power transfer system (WPT). The pancake coil, spiral coil and solenoid coil designs were proposed, whose study were carried out based on the Finite Element Method in 2D using H-formulation. The transport current loss in each layer for each coil when applying high-frequency AC current were simulated in the FEM platform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In recent years, research has been conducted to establish magnetic resonance radio energy transmission systems using high-quality factor superconducting coils as resonant coils, which improves the energy transmission performance of the systems. The research on high-temperature superconducting WPT systems has mainly focused on coil structure design and transmission efficiency [5][6][7][8][9][10]. Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, research has been conducted to establish magnetic resonance radio energy transmission systems using high-quality factor superconducting coils as resonant coils, which improves the energy transmission performance of the systems. The research on high-temperature superconducting WPT systems has mainly focused on coil structure design and transmission efficiency [5][6][7][8][9][10]. Ref.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [7], the investigation of the effect of various HTS coil configurations on the transmission performance of WPT systems revealed that flat coil and spiral coil designs can be effectively applied to relatively low-frequency WPT systems. On the other hand, the solenoid coil design can achieve the lowest total loss in WPT system applications operating at higher frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…The main technological applications range from superconducting fault current limiter for use in electric power system to wireless power transfer for use in electric vehicle. A plethora of features have been investigated such as transport current and magnetization losses [12,13]; charging, discharging and overcurrent [14][15][16]; turn-to-turn contact resistance [17]; interfacial stress and critical current degradation [18,19]; axial levitation force [20]; bifilar coil and transformer magnetic shield for superconducting fault current limiter [21,22]. Although there are many works on the subject, the study on the nonlinearity of the inductance is scarce.…”
Section: Introductionmentioning
confidence: 99%